Measuring GitHub Copilot's Impact on Productivity. - Ziegler, Albert; Kalliamvakou, Eirini; Li, X. Alice; Rice, Andrew; Rifkin, Devon; Simister, Shawn; Sittampalam, Ganesh; Aftandilian, Edward (Communications of the ACM, 2024)
The article looks at the effects of the use of the code completion tool GitHub's Copilot on developer productivity. According to the authors, this is the first code suggestions tool study showing a correlation between usage measurements and developer productivity. The five dimensions of productivity (SPACE) include Satisfaction and well being, Performance, Activity, Communication and collaboration, and Efficiency and flow are also discussed.